2021
DOI: 10.1002/jimd.12448
|View full text |Cite
|
Sign up to set email alerts
|

Methionine synthase deficiency: Variable clinical presentation and benefit of early diagnosis and treatment

Abstract: Methionine synthase deficiency (cblG complementation group) is a rare inborn error of metabolism affecting the homocysteine re-methylation pathway. It leads to a biochemical phenotype of hyperhomocysteinemia and hypomethioninemia. The clinical presentation of cblG is variable, ranging from seizures, encephalopathy, macrocytic anemia, hypotonia, and feeding difficulties in the neonatal period to onset of psychiatric symptoms or acute neurologic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 32 publications
0
9
1
Order By: Relevance
“…However, cobalamin deficiency can occur at the cellular level even with normal serum cobalamin concentrations, 26 and cobalamin supplementation can improve HCC even in patients without overt hypocobalaminemia. 27 Serum folate concentrations were below the lower limit of the reference interval (7.7 μg/L) in approximately 55% (16 of 29) of the healthy Greyhounds in our study. Although not significantly different from controls, serum folate concentrations were inversely correlated with serum HCy concentrations.…”
Section: Discussioncontrasting
confidence: 57%
See 2 more Smart Citations
“…However, cobalamin deficiency can occur at the cellular level even with normal serum cobalamin concentrations, 26 and cobalamin supplementation can improve HCC even in patients without overt hypocobalaminemia. 27 Serum folate concentrations were below the lower limit of the reference interval (7.7 μg/L) in approximately 55% (16 of 29) of the healthy Greyhounds in our study. Although not significantly different from controls, serum folate concentrations were inversely correlated with serum HCy concentrations.…”
Section: Discussioncontrasting
confidence: 57%
“…In our Greyhounds, however, only 1 dog had a serum cobalamin concentration below the lower limit of the reference interval, suggesting that low serum cobalamin concentrations are unlikely to be the primary driver of HHC in Greyhounds. However, cobalamin deficiency can occur at the cellular level even with normal serum cobalamin concentrations, 26 and cobalamin supplementation can improve HCC even in patients without overt hypocobalaminemia 27 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolite set enrichment analysis in Gad2 Fgf13 KO vs. WT (Supplemental Table 1) revealed that the most enriched Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway among upregulated metabolites was glycolysis (P=4.29E-6), also consistent with data obtained in patients in status epilepticus (Hanin, Chollet et al 2024). The most downregulated pathway was methionine metabolism (P=9.88E-4), consistent with methionine synthase deficiency-an inborn error of metabolism-that present with seizures (Kripps, Sremba et al 2022). Thus, this metabolomic analysis supported the severity of the seizure phenotype observed in Gad2 Fgf13 KO mice.…”
Section: Inhibitory Neuron Knockout Of Fgf13 Recapitulates Spontaneou...mentioning
confidence: 63%
“…As shown in the proband, it has previously been reported that the cblG phenotype can be present with neurological symptoms (43)(44)(45)(46)(47). Komulainen-Ebrahim et al and Kripps et al observed the neurological symptoms as a result of methionine synthase deficiency, along with the need for early treatment to reduce the neurological symptoms (48,49).…”
Section: Discussionmentioning
confidence: 91%